Digitalization potentials in supporting offshore wind logistics - Sylvain Chartron; Michael Stein; Jérôme Gaysse; Hans-Dietrich Haasis (Logistics 4.0 and Sustainable Supply Chain Management: Innovative Solutions for Logistics and Sustainable Supply Chain Management in the Context of Industry 4.0. Proceedings of the Hamburg International Conference of Logistics (HICL), Vol. 26, 2018)
Digitalization complementing offshore wind energy is a topic of interest for both researchers and practitioners. As part of a broader research on offshore wind logistics optimization, this paper focuses on how digitalization can be further developed to support logistics in the particular domain of offshore wind farm construction, as well as Operations and Maintenance (O&M). This paper analyzes five major digitalization potentials: the use of unmanned systems, 3D printing, motion sensors, big data techniques and LiDAR usage. The term Industrial Digitalization Technologies (IDT) summarizes these potentials. This contribution provides an initial mixed method analysis on enhanced offshore wind efficiency. Initial frameworks based on in-depth literature analysis on the one hand and on experimental break-even calculations on the other, are provided. This paper's outcome shows that unmanned systems provide the by far largest cost-saving potential.
urn:nbn:de:gbv:830-88223515; 10419/209195; https://econpapers.repec.org/RePEc:zbw:hiclpr:26
Keywords: 650; Digitalization; Offshore wind logistics; Optimization; LCOE